Le emissioni delle banche italiane sull’euromercato (The Eurobond Issues of Italian Banks) - Paolo Emilio Mistrulli (Moneta e Credito, 2012)
After the launch of the single European currency banks of the main euro-area countries have increasingly issued bonds on the Euromarket. In this paper, I investigate the determinants of Italian banks' recourse to international capital markets. I find that, other things being equal, domestic market conditions affect the choice whether to issue Eurobonds. In particular, the econometric analysis highlights that those banks, which are more prone to issue bonds on the Euromarket, are more exposed to liquidity risks and are less specialized in raising deposits on specific domestic submarkets.